Credit where it is due: Investigating pathways from earned income tax credit expansion to maternal mental health. (29th June 2020) - Gangopadhyaya, Anuj; Blavin, Fredric; Braga, Breno; Gates, Jason
Abstract: While earned income tax credit (EITC) expansions are typically associated with improvements in maternal mental health, little is known about the mechanisms through which the program affects this outcome. The EITC could primarily affect mental health through changes in family financial resources, changes in labor supply or changes in health insurance coverage of participants. We attempt to disentangle these mechanisms by assessing the effects of state and federal EITC expansion on mental health, employment, and health insurance by maternal marital status. We find that federal EITC expansions are associated with improved self‐reported mental health for all mothers and large positive effects on employment for unmarried mothers. State EITC expansions are associated with improvements in mental health for married mothers only and have no effect on employment for married or unmarried mothers. Overall and for most subgroups of mothers, we find little association between EITC expansions and changes in health insurance coverage. These findings suggest that while EITC expansions improved mental health for unmarried mothers through a combination of the credit and employment effects, for married mothers, improved mental health is driven through the direct credit alone.